Associations between Graduated Driver Licensing restrictions and delay in driving licensure among U.S. high school students. (June 2021) - Vaca, Federico E.; Li, Kaigang; Fell, James C.; Haynie, Denise L.; Simons-Morton, Bruce; Romano, Eduardo
Abstract: Introduction: Some of the most vulnerable groups of teens choose to delay driving licensure (DDL). We assessed longitudinal associations between state-level Graduated Driver Licensing (GDL) restrictions and DDL among U.S. high school students. Methods: Data from seven waves of the NEXT Generation Health Study (starting 10 th -grade (2009–2010)), were analyzed in 2020 using Poisson regression. The outcome was DDL (delay vs. no-delay). Independent variables were driving restrictions (at learner and intermediate phases of licensure), sex, race/ethnicity, family affluence, parent education, family structure, and urbanicity. Results: Of 2525 eligible for licensure, 887 (38.9%), 1078 (30.4%), 560 (30.7%) reported DDL 1–2 years, >2 years, no DDL, respectively. Interactions between GDL restrictions during the learner permit period and covariates were found. In states requiring ≥30 h of supervised practice driving, Latinos (Adjusted relative risk ratio [aRRR] = 1.55, p < .001) and Blacks (aRRR = 1.38, p < .01) were more likely to DDL than Whites. In states where permit holding periods were <6 months, participants with low (aRRR = 1.61, p < .001) and moderate (aRRR = 1.45, p < .001) vs. high affluence were more likely to DDL. Participants in single-parent households vs. both-biological parent households were also more likely to DDL (aRRR = 1.37, p < .05). In states where permit holding periods were ≥6 months, participants with low (aRRR = 1.33, p < .05) vs. high affluence were more likely to DDL. In states that allowed ≥3 passengers or no passenger restriction, participants living in non-urban vs. urban (aRRR = 1.52, p < .05) areas were more likely to DDL, and in states that allowed only 1 or no passenger, participants living in non-urban vs. urban areas (aRRR = 0.67, p < .001) were less likely to DDL. Conclusions: Our findings heighten concerns about increased crash risk among older teens who age out of state GDL policies thereby circumventing driver safety related restrictions. Significant disparities in DDL exist among more vulnerable teens in states with stricter GDL driving restrictions. Highlights: Graduated Driver Licensing (GDL) programs are associated with reduced fatal crash. Some of the most vulnerable groups of teens choose to delay driving licensure (DDL). Teens aging out of state GDL may circumvent driver safety related restrictions. Significant disparities in DDL exist in states with stricter GDL driving restrictions.